The Impact of Early Exposure to Urology: Evaluation of an Introductory Preclinical Course. Issue 4 (8th July 2020) - Greenberg, Daniel R.; Conti, Simon L.; Shah, Jay B.
Abstract: Introduction: Early exposure in medical school can increase student interest in urology. The majority of medical students graduate without completing a clinical rotation in this field. The primary objectives of our study were to increase exposure to urology and to facilitate interactions between preclinical students and department faculty. Methods: A 7-week urology curriculum consisting of a weekly 1-hour class was introduced into the M.D. curriculum. Lectures were taught by faculty, fellows and resident physicians, and focused on the professional trajectory of the speaker, a career in urology, information on urological subspecialties and teaching points relevant to each topic. Pre/post surveys were administered to evaluate the effectiveness of the course. Results: A total of 16 students enrolled in the course. Before this course the majority of students had less than 1 hour of teaching focused on urological topics. Informal exposure to urology was similar between preclinical students and graduating fourth year medical students (p >0.05). Post-course surveys showed that students had increased exposure to urology, greater opportunity to interact with residents, fellows and faculty, and overall they were satisfied with their course experience. Students who attended 4 or more courses reported they understood what a career in urology entails and had acquired the necessary information to decide whether to enroll in a clinical rotation in urology. Conclusions: This course increased exposure to urology among preclinical students and is a feasible addition to a standard medical school curriculum. Future studies will follow these students longitudinally and determine if this course increases student enrollment in urological clinical rotations and increases urology residency applications.